Stereotaktische Strahlentherapie von Lebermetastasen - Herfarth, Klaus; Debus, Jürgen (Der Chirurg, 2005)
Advances in radiation oncology made possible the locally curative treatment approach of stereotactically guided radiation therapy of liver tumours. Results of this highly focussed therapy were published by only a few centres. The radiation dose is delivered in one or a few fractions with high single doses. All published results show high local tumour control with low treatment morbidity. The treatment results of this noninvasive technique are similar to those of minimally invasive ablative therapies. Our own and other published data are summarized and discussed. The long-term results of this technique are currently being evaluated in a prospective multicentre trial.